Childhood in the hiding place of the poet's soul : An analytical study of children's expression in poetry - كه‌ریم حسێن, سالار (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
the summary of this research which is called: (the childhood in the hideout of poet`s soul), we find out that in Kurdish literature, there is a special type of poem that is written with a childish sense and spirit, at the same time it is highly philosophical and a deep level of artistic and logic can be seen from them. Using such technique by our poets refers to having a high awareness and deep knowledge by them which made them pass the limit of poem through this form of writing poems, to finally create a text that is full of delight and meaning, in a way its form looks childish and simple yet its context is full of wisdom and deep meanings, to this purpose they used the embodiment of children’s psychology and behavior, to give their poems the sense of children’s magical world.